Complicity in fin-de-siècle literature / Helen Craske. - Craske, Helen (Oxford modern languages and literature monographs., 2024)
This volume examines the representation and creation of shared crime and guilt in late nineteenth-century France: exploring how particular genres - from murder fiction to saucy magazines - encouraged the creation of collusive relationships between writers, readers, and critics.